Missionary tasks of the first Russian consulate in Japan (1858–1865) - Andrey Stepanov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article is devoted to the missionary activities of the first Russian consulate in Japan (1858-1865). The thesis stated is the importance of the missionary factor at the initial stage of Russian-Japanese relations. When writing the article there was implemented the analysis of research literature, letters and memos of the main participants of Russian-Japanese relations. The continuity of the consulate's activities with the diplomatic and missionary activities of E.V.Putyatin in the context of the foreign policy of the Russian Empire in China and Japan is revealed. The influence of Putyatin on the decisions of the Amur Committee, which was expressed in concrete proposals for the formation of the staff of the consulate and the directions of its work on the implementation of the missionary task, is considered. The thesis is proved that the first Consul I.A.Goshkevich possessed the necessary qualities of a diplomat and a missionary and therefore was able to fully realize the duties assigned to him. The assistance of the Asian Department of the Ministry of Foreign Affairs to the Holy Synod and the Chief Prosecutor is noted. Letters from Putyatin and Hieromonk Nikolai (Kasatkin) to Goshkevich testify to the use of the hospital and school at the consulate for missionary purposes. The facts and sources considered in the article allow us to draw conclusions about the significance of the experience of the first consulate in Japan for understanding the problems of the theology of the mission: the missionary task of the consulate is assessed as the implementation by Putyatin of the religious and political modelfor Orthodoxy expansion; social and educational activities - as a created missionary environment (macromission). The close connection between the missionary aspect and the solution of foreign policy goals (the establishment of good-neighborly relations between the two countries) is shown, where the state, participating in the spread of the Kingdom of Christ, performed a providential task in the context of the entire Christian history.